Sublime disorder - Curran, A (Voltaire Foundation, 2017)
This work places Diderot’s fascination with anatomical anomalies or monsters within the context of the history of ideas, philosophy, and science. By chronicling the ideological component of the philosophe’s presentation of monstrosity from the Lettre sur les aveugles to Le Neveu de Rameau, this book reveals Diderot’s ‘random and accidental’ monsters to be, ironically, the most teleological of all beings: created and staged, as it were, for a particular textual world where materialist dogma is as important as disinterested anatomical study. Acknowledgements Abbreviations Introduction 1 From Providence to chance: the emergence of monstrosity in Diderot’s universe 2 Diderot’s revisionism: blindness and Enlightenment in the Lettre sur les aveugles 3 Monsters and the self in Le Rêve de d’Alembert 4 Ethical monstrosity and the Enlightenment’s rejeton Jean-François Rameau Conclusion Bibliography Index